Comparison of Early Maladaptive Schemas and Coping Strategies among People with Obsessive-Compulsive Personality Disorder and Normal People - Babak Keshvari; Gholamreza Sanagouye-Moharer (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: One of the main components of obsessive-compulsive disorder is disturbing thoughts. Cognitive infrastructures, schemas and avoidance coping styles in obsessive-compulsive disorder have always been the subject of attention by clinical psychologists. The purpose of the present study was to compare early maladaptive schemas and coping strategies among people with obsessive-compulsive personality disorder and normal people. Materials and Methods: The present study was of casual-comparative style. The statistical population of this study included patients with obsessive-compulsive disorder referred to psychiatry and psychiatric clinics in Tehran in 2017 and a control group. Among 140 patients, 70 obsessive-compulsive disorders and a control group of 70 participants were selected through convenience sampling. Data were collected using MCMI-III Questionnaire, Coping Strategies Questionnaire and early Maladaptive Schema Questionnaire. Data analysis was performed using multivariate analysis of variance using SPSS software version 18. Results: The mean (SD) age of the obsessive-compulsive group was 37.6 (8.4) and the control group 35.2 (7.8). The mean (SD) score of the coping style of submission was 418.3 (107), extreme compensation 152.4 (20.7) and avoiding 133.8 (18.4) in participants with obsessive-compulsive disorder which were higher than the control group: submission 382.5 (97.3), extreme compensation is 136.8 (16.2) and avoidance of 109.6 (12.1). In the obsessive-compulsive group, the score of components of the emancipatory/unstable schemas was 17.2 (6.8), unreliability/mistreatment (19.3), emotional deprivation (20.9) (7.8), deficit/shame 7.18 (5.7), and social isolation 16.16 (9.8) which were higher than the control group: abandonment/unstable 14/14 (1.5), unreliability/mistreatment 12/6 (4.6), emotional deprivation 7.13 (7.1), defect/shame 11.11 (2.5) and social isolation 2.12 (7), P<0.001. The level of impact or difference is 0.42 which implied that 42% of the individual differences in the scores of the subscales of the research were related to the impact of group membership. Conclusion: It can be concluded that mean scores of early maladaptive schemas of relapse/insecurity, lack of trust/mistreatment, emotional deprivation, defect/shame and social isolation and coping styles of avoidance, extreme compensation and submission of the obsessive-compulsive group are higher than the average the control group. DOI: http://doi.org/10.22037/ch.v6i4.23119